Energy Cost of Running Under Hypogravity in Well-Trained Runners and Triathletes: A Biomechanical Perspective - Ueberschär O.; Fleckenstein D.; Warschun F.; Walter N.; Wüstenfeld J. C.; Wolfarth B.; Hoppe M. W. (International Journal of Computer Science in Sport)
Hypogravity treadmills have become a popular training tool in distance running and triathlon. Counter-intuitively, tibial acceleration load is not attenuated by hypogravity unloading during running, while, equally surprisingly, leaps become flatter instead of higher. To explain these effects from a biomechanical perspective, Polet, Schroeder, and Bertram (2017) recently developed an energetic model for hypogravity running and validated it with recreational athletes at a constant jogging speed. The present study was conducted to refine that model for competitive athletes at relevant running speeds of 12–22 km h−1 and gravity levels of 100 %, 80 % and 60 %. Based on new experimental data on 15 well-trained runners in treadmill tests until volitional exhaustion, the enhanced semi-empirical model well describes energy expenditure and the observed biomechanical effects of hypogravity running. Remarkably, anaerobic contributions led to an increase in energy cost per meter for speeds above 16–18 km h−1 (p < 0.001), irrespective of hypogravity unloading. Moreover, some converging trends were observed that might reflect general adaptations in running motor control for optimization of efficiency. In essence, the outcome of this research might help sports scientists and practitioners to design running programs for specific training stimuli, e.g. conditioning of anaerobic energy metabolism.